The third industrial revolution : how lateral power is transforming energy, the economy, and the world - Rifkin, Jeremy. 4 0 16; 5 (New York : Palgrave Macmillan, 2011)
Rifkin explores how Internet technology and renewable energy are merging to create a powerful Third Industrial Revolution by giving an inside account of the next great economic era, including a look into the personalities and players -- heads of state, global CEOs, social entrepreneurs, and NGOs -- who are pioneering its implementation around the world.
Includes bibliographical references (pages [271]-286) and index.
Publisher's Weekly, June 2011
Adult;Adult.
Keywords: 2 -- 0; 6; Environmental aspects. -- Energy development.;Power resources;Industries. -- 20; 20; 2